Singapore : Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
This Statistical Appendix report on Singapore discusses the economic indicators for the period 1995-99. The report includes expenditure on gross domestic product; changes in productivity and earnings; unit labor costs; consumer price index; foreign direct investment inflows by industry; assets and liabilities of the Monetary Authority of Singapore; assets and liabilities of commercial banks of Singapore; summary of balance of payments; export and import performance; services and income accounts; transfer payments; and so on.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet